Studi Komparasi Penyebaran Berita Bohong (Hoax) Perspektif UU ITE dan Hukum Pidana Islam - Rofiatul Maghfiroh; Raffid Abbas (Rechtenstudent, 2020)
A large number of internet users in Indonesia and the high frequency of accessing information and news content on social media do not necessarily guarantee the maturity of their users. A lot of hoax content that is rife happened because of the absence of news selection. The purpose of this study was to determine the comparison of the sanctions for the perpetrators of spreading fake news on social media in Law Number 19 of 2016 concerning Information and Electronic Transactions and Islamic Criminal Law. The author uses a normative approach (statute approach) which is carried out with a statutory approach, a conceptual approach (conceptual approach), and an analytical approach (analytical approach). The spread of fake news (hoax) is prohibited in positive law and Islamic law. In positive law regulated in Law Number 19 of 2016, amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions are contained in Article 28 paragraph (1) and (2), 27 paragraph (3) and Article 45A paragraph (1 ) and (2) with the threat of a maximum imprisonment of 6 (six) years and / or a maximum fine of Rp. 1,000,000,000.00 (one billion). Meanwhile, in Islamic criminal law, the spread of fake news (hoax) is not allowed. Islam advises its followers to speak well and truthfully (shiddiq), not someone who is in a hurry to share news and not one who reverses the facts. In Islamic Criminal Law itself, the sanction given to perpetrators who spread fake news is Ta'zir.